2012
DOI: 10.1088/2043-6262/3/3/035014
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence biosensor based on CdTe quantum dots for specific detection of H5N1 avian influenza virus

Abstract: This report highlights the fabrication of fluorescence biosensors based on CdTe quantum dots (QDs) for specific detection of H5N1 avian influenza virus. The core biosensor was composed of (i) the highly luminescent CdTe/CdS QDs, (ii) chromatophores extracted from bacteria Rhodospirillum rubrum, and (iii) the antibody of β-subunit. This core part was linked to the peripheral part of the biosensor via a biotin-streptavidin-biotin bridge and finally connected to the H5N1 antibody to make it ready for detecting H5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Zero-dimensional quantum dots (QDs) are the quasi spherical NPs belong to the family of inorganic semiconducting NPs that have been broadly investigated during the past decade. Their significant applications in material and biological science have been well investigated [ 74 , 75 , 76 , 77 ]. A number of quantum dots, e.g., CdSe, CdS, CdTe, ZnO, ZnSe, PbS, PbSe, SnS, InP, InS, InN and so on, have been extensively considered for different physical properties.…”
Section: Nanoparticles In Discotic Liquid Crystalsmentioning
confidence: 99%
“…Zero-dimensional quantum dots (QDs) are the quasi spherical NPs belong to the family of inorganic semiconducting NPs that have been broadly investigated during the past decade. Their significant applications in material and biological science have been well investigated [ 74 , 75 , 76 , 77 ]. A number of quantum dots, e.g., CdSe, CdS, CdTe, ZnO, ZnSe, PbS, PbSe, SnS, InP, InS, InN and so on, have been extensively considered for different physical properties.…”
Section: Nanoparticles In Discotic Liquid Crystalsmentioning
confidence: 99%
“…They also present narrow and tunable emission spectra and usually present good photostability, which substantially increase their hall of applications. Nguyen et al [23] described a CdTe quantum dotbased biosensor, developed specifically to detect flu virus H5N1. They reported that the biosensors consisted of CdTe/CdS quantum dots of high quantum yield, chromatophores extracted from a bacteria and of β-subunit antibody, all connected to a protein, which was, then, connected to the H5N1 antibody.…”
Section: Supramolecular Compounds For Optical Biosensorsmentioning
confidence: 99%
“…They reported that the biosensors consisted of CdTe/CdS quantum dots of high quantum yield, chromatophores extracted from a bacteria and of β-subunit antibody, all connected to a protein, which was, then, connected to the H5N1 antibody. They recorded the changes in the QD photoluminescence spectra and collected images of the QD-labelled chromatophores in an optical microscope to evaluate the specificity of the biosensor [23].…”
Section: Supramolecular Compounds For Optical Biosensorsmentioning
confidence: 99%
“…Biosensors, which combine a target-specific biological element with a transducer and signal processing unit, have shown great promise in their applications for pathogen detection in food safety, environmental monitoring, and clinical diagnostics. Some biosensors have been reported for the detection of AIV using methods such as surface plasmon resonance [ 5 , 6 , 7 , 8 , 9 ], quartz crystal microbalance [ 10 , 11 , 12 , 13 ], fluorescence [ 14 , 15 ], optical interferometry [ 16 ], imaging ellipsometry [ 17 ], and electrochemistry [ 18 , 19 , 20 ]. Recently, Jarocka’s group developed an electrochemical immunosensor for detection of antibodies against AIV H5N1 in hen serum [ 21 ].…”
Section: Introductionmentioning
confidence: 99%